The Effect of Refugees on Native Adolescents' Test Scores: Quasi-Experimental Evidence from Pisa - Semih Tumen (Institute of Labor Economics (IZA), 2021)
Existing evidence suggests that low-skilled refugee influx may increase educational attainment among native adolescents due to reduced opportunities and returns in the lower segment of the labor market. In this paper, I test whether refugee influx can also increase the intensity of human capital accumulation among native adolescents who are enrolled in school. Using the PISA micro data and implementing a quasi-experimental empirical strategy designed to exploit (i) the time variation in regional refugee intensity and (ii) institutional setting in the Turkish public education system, I show that the Math, Science, and Reading scores of Turkish adolescents increased following the Syrian refugee influx. The increase in test scores mostly comes from the lower half of the test score distribution and from native adolescents with lower maternal education. The empirical design embeds a framework where the estimated refugee impact can solely be attributed to the labor market mechanism. In particular, I use the observation that refugee adolescents are enrolled more systematically into the Turkish education system after 2016, which gave me the opportunity to use 2015 and 2018 PISA waves in a way to isolate the the effect of the labor market mechanism from the potentially negating force coming from the education experience mechanism. I conclude that the labor market forces that emerged in the aftermath of the refugee crisis have led native adolescents, who would normally perform worse in school, to take their high school education more seriously.
Keywords: I21; I25; I26; J61; 330; Syrian refugees; test scores; PISA; labor markets